THE MORBIDITY WITH TEMPORARY DISABILITY OF WORKING MILITARY RETIREES - A. V. Popov (Исследования и практика в медицине)
The purpose of the study. The study of morbidity with temporary disability of working officers of the Navy, retired and resigned, as well as affecting the level of certain factors.Materials and methods. A sociological survey of 574 officers of the Navy, who were dismissed from the Armed Forces to the reserve (resignation), was held. 32.7% of them at the time of the survey have been working.Results. 48.8% of respondents rated their health at the time of the survey as a good for their age. The level of morbidity with temporary disability (MWTD) in 100 operating reserve (retired) officers amounted to 94 cases. The number of days of temporary disability was equal to 867 days per 100 employed military pensioners. Most long-term treatment (up to 47 days) were required for patients with blood diseases. Analysis of the structure of diseases of reserve (retired) officers leading to temporary disability, showed that the bulk of the cases (63.7 per cent) were diseases of the respiratory organs, in second place were diseases of the circulatory system (24,5%), the third — diseases of the genitourinary system (4.3%). The average number of existing diseases to working military retirees less than idle: 1.9 vs 2.1. The average number of diseases at the single soldiers discharged was significantly more than that of living in family.Conclusion. The features of level and structure, as well as risk factors of MWTD should be considered in the development and adoption of administrative decisions directed on preservation and strengthening of health of reserve (retired) officers.